Analysis Of The Existing Geometric Design Conditions Of The Bypass Of The City Of San Juan De Pasto – Nariño – Colombia - Luis Armando Merino Chamorro; Jorge Luis Argoty Burbano (Kurdish Studies, 2022)
The present work written in the development, summarizes and describes the theoretical foundation, accompanied by the analysis procedure for one of the routes under study that constitute the variant of the city of San Juan de Pasto, this for each parameter object of analysis, at the end some conclusions and recommendations are presented, as well as comparative statistical graphs of the most important parameters and on plans critical points of the design are indicated as an annex. This is done both for the actual design speed (the speed with which the design was carried out) and for the minimum theoretical design speed (the speed that, due to the conditions under which the project is developed, should have been chosen based on the provisions of the Manual for the Geometric Design of Roads). This analysis aims to generate conclusions and some recommendations regarding the existing design of the bypass of the city of San Juan de Pasto, which begins in the township of Catambuco and ends in the sector of the Daza tunnel.